2021
DOI: 10.1055/a-1213-2245
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporose-Update 2021

Abstract: Was ist neu? Romosozumab Romosozumab ist ein humanisierter Antikörper gegen das Osteozyten-spezifische Protein Sklerostin. Die Neutralisierung von Sklerostin mit Romosozumab fördert die Knochenneubildung. Die schnelle Zunahme an Knochenmasse reduziert deutlich das Frakturrisiko und geht bereits nach einem Jahr in ein Plateau über. Als Erhaltungstherapie ist eine anschließende antiresorptive Therapie erforderlich. Romosozumab ist zugelassen als neues anaboles Wirkprinzip für die Behandlung der schwere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In foreign literature, we can find the term "silent disease" when the scientists talk about "osteoporosis" [1,8,9]. Elderly and senile ages are critical periods for the development of osteoporosis and its complications -low-energy osteoporotic fractures, the most severe of which is a hip fracture, the occurrence of which leads to prolonged disability and death of the patients [2,[8][9][10]. Additionally, the presence of other osteoporotic fractures, that are vertebral ones, often leads to back pain and reduced work capacity of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In foreign literature, we can find the term "silent disease" when the scientists talk about "osteoporosis" [1,8,9]. Elderly and senile ages are critical periods for the development of osteoporosis and its complications -low-energy osteoporotic fractures, the most severe of which is a hip fracture, the occurrence of which leads to prolonged disability and death of the patients [2,[8][9][10]. Additionally, the presence of other osteoporotic fractures, that are vertebral ones, often leads to back pain and reduced work capacity of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…During aging, the risk of various diseases increases in a person, as there are age-related changes in various organs and systems. Bone system aging is characterized by the development of degenerative-dystrophic and metabolic changes that lead to the development of osteoporosis and its complications - low-traumatic fractures, which not only reduce the working capacity of the patients and limit their daily capabilities, but also lead to an increase in mortality rates due to low-traumatic fractures [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ageing of the musculoskeletal system is characterized by the development of degenerative-dystrophic and metabolic changes, leading to the development of osteoporosis and sarcopenia, which are characterized by generalized loss of bone and muscle tissue. These conditions not only increase the risk of low-energy fractures and falls but also lead to a decrease in the functional activity of the patients, and their disability, and an increase in mortality rates [1,2,3,4,5,6,7].…”
mentioning
confidence: 99%
“…Currently, assessment of bone mineral density (BMD) and quality of bone tissue, measured using dual-energy X-ray absorptiometry (DXA), can provide a reliable estimate of bone strength and the risk of osteoporotic fractures. It has been demonstrated that BMD determines approximately 70-75% of bone strength, and according to recommendations from leading global organizations (ISCD, IOF), it is used to diagnose osteoporosis [1,2].…”
mentioning
confidence: 99%